Effects of total parenteral nutrition on drug metabolism gene expression in mice - Christina Ferrucci-Da Silva; Le Zhan; Jianliang Shen; Bo Kong; Michael J. Campbell; Naureen Memon; Thomas Hegyi; Lucy Lu; Grace L. Guo (Elsevier, 2020)
Parenteral nutrition-associated liver disease (PNALD) is a liver dysfunction caused by various risk factors presented in patients receiving total parenteral nutrition (TPN). Omega-6 rich Intralipid® and omega-3 rich Omegaven® are two intravenous lipid emulsions used in TPN. TPN could affect the hepatic expression of genes in anti-oxidative stress, but it's unknown whether TPN affects genes in drug metabolism. In this study, either Intralipid®- or Omegaven®-based TPN was administered to mice and the expression of a cohort of genes involved in anti-oxidative stress or drug metabolism was analyzed, glutathione (GSH) levels were measured, and protein levels for two key drug metabolism genes were determined. Overall, the expression of most genes was downregulated by Intralipid®-based TPN (Gstp1, Gstm1, 3, 6, Nqo1, Ho-1, Mt-1, Gclc, Gclm, Cyp2d9, 2f2, 2b10, and 3a11). Omegaven® showed similar results as Intralipid® except for preserving the expression of Gstm1 and Cyp3a11, and increasing Ho-1. Total GSH levels were decreased by Intralipid®, but increased by Omegaven®. CYP3A11 protein levels were increased by Omegaven®. In conclusion, TPN reduced the expression of many genes involved in anti-oxidative stress and drug metabolism in mice. However, Omegaven® preserved expression of Cyp3a11, suggesting another beneficial effect of Omegaven® in protecting liver functions. Key words: Total parenteral nutrition, Glutathione, Drug metabolism, Liver, Parenteral nutrition-associated liver disease